Providing senior design students with a clinical perspective. - Goldberg, J.R (IEEE Engineering in medicine and biology magazine)
This article aims to provide students with a clinical perspective of medical device design. This study shows that it is not only important for students to understand how medical devices are designed and function but how these devices are used by patients, physicians, surgeons, nurses, and physical therapists too. For implantable devices, this includes problems associated with the preparation, insertion, and removal of devices in a patient's body. For monitoring or imaging equipment, this includes problems associated with device set up and operation and interpretation of data. This knowledge is important to medical device designers who may be able to avoid or solve many of these problems through good design.